A reproducible grading scale for histological assessment of inflammation in ulcerative colitis. Issue 3 (1st September 2000) - Geboes, K; Riddell, R; Öst, A; Jensfelt, B; Persson, T; Löfberg, R
Abstract : BACKGROUND: Evaluation of histological activity in ulcerative colitis needs to be reproducible but has rarely been tested. This could be useful both clinically and in clinical trials. AIM: To develop reproducible criteria which are valid in the assessment of acute inflammation (activity) and chronicity, and to evaluate these features in an interobserver variability study. METHODS: A six grade classification system for inflammation was developed which could also be fine tuned within each grade. The grades were: 0, structural change only; 1, chronic inflammation; 2, lamina propria neutrophils; 3, neutrophils in epithelium; 4, crypt destruction; and 5, erosions or ulcers. Ninety nine haematoxylin-eosin sections from endoscopically inflamed and non-inflamed mucosa from patients with distal ulcerative colitis were assessed in two separate readings by three pathologists independently and without knowledge of the clinical status. Interobserver agreement was compared pairwise using kappa statistics. RESULTS: Initially, kappa values between the observers were 0.20, 0.42, and 0.26, which are too low to be of value. Following development of a semiquantitative pictorial scale for each criterion, kappa values improved to 0.62, 0.70, and 0.59. For activity defined by neutrophils between epithelial cells, kappa values were 0.903, 1.000, and 0.907. Complete agreement was reached in 64% of samples of endoscopically normal and in 66% of endoscopically inflamed tissue. Neutrophils in epithelium correlated with the presence of crypt destruction and ulceration. CONCLUSION: A histological activity system was developed for ulcerative colitis that showed good reproducibility and modest agreement with the endoscopic grading system which it complemented. It has potential value both clinically and in clinical trials.